INVESTIGATING YEMENI EFL LEARNERS’ INVOLVEMENT IN CLASSROOM ORAL ACTIVITIES AND ITS CORRELATION TO THEIR SPEAKING PROFICIENCY DEVELOPMENT - Sabri Thabit Saleh Ahmed (Indonesian Journal of Learning and Instruction)
This study investigated Yemeni EFL learners’ involvement in classroom oral activities and its correlation to their speaking proficiency development with a reference to three rural faculties of education affiliated to Aden University. The data was collected through a questionnaire which targeted 120 fourth-year EFL learners. The results revealed that the students’ involvement in classroom activities is pretty low. It has been unveiled that pair work and group work activities are not implemented in a regular basis and it is limited to a few students. The findings also showed a significant correlation between learners’ involvement in classroom oral activities and their speaking proficiency (p. value 0.05%). As per these findings, this study recommends the concerned faculties to implement communicative language teaching in their EFL programs to ensure students’ engagement in classroom activities and promote their oral proficiency.